18F FDG PET-CT in the Diagnosis of Spinal Cord Involvement Secondary to Non Hodgkins Lymphoma– A Case Report - Begum, Shamim MF; Begum, Fatima; Hussain, Raihan; Sarker, Azmal Kabir; Hasan, Mizanul (Bangladesh Journal of Nuclear Medicine, 2018)
Spinal cord involvement secondary to non Hodgkin lymphoma (NHL) is rare and associated with quick development of neurological defects. The overall risk of central nervous system relapse in aggressive NHL ranges 2%–27% and is associated with a poor prognosis. Hence early detection is important for staging and prognostication. Magnetic Resonance Imaging (MRI) is the routinely used potential imaging modality for spinal cord metastasis. Several studies have shown the values of 18F FDG (flurodeoxyglucose) PET- CT for staging, restaging, and therapy monitoring in NHL. PET has 96% sensitivity in the detection spinal metastasis. This reported case was a 35 years old male, diagnosed as peripheral T cell lymphoma on June 2014 and was treated with chemotherapy. In January 2016 he developed swelling of lower limbs and paraparesis with bladder and bowel involvement. Duplex color Doppler of lower limbs showed normal flow and Complement Fixation Test for filariasis was negative. MRI T2W showed hyper intensity signal extending from lower cervical to all dorsal cord. The 18F FDG PET-CT was performed to restage the disease and showed intense FDG uptake in the spinal cord, extended from the lower cervical to 11th thoracic and at the level of 3rd and 4th lumbar vertebrae. The spinal cord hypermetabolism observed on PET CT scan correlated with MRI characteristics and significantly aided in the diagnosis of spinal cord involvement. This case is reported to emphasize the usefulness 18F FDG PET-CT in restaging and follow-up of patients with NHL. PET-CT imaging can reliably identify hyper-metabolic central nervous system involvement and help not only to restage patients but also to guide new therapeutic strategies. Bangladesh J. Nuclear Med. 19(2): 146-148, July 2016